2020
DOI: 10.1149/1945-7111/aba00b
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Oxide Growth During Ti Galvanostatic Anodization

Abstract: The mechanism of TiO 2 nanotubes has attracted increasing attention. However, relationships between the anodizing parameters and nanotube size (or oxide volume) have been rarely studied. The traditional field-assisted dissolution theory can only qualitatively explain the cause of the pore formation but cannot quantitatively explain the relationship between the growth height of nanotubes and the anodizing current. Here, the growing processes of TiO 2 nanotubes in four current at three different NH 4 F concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…31 Zhang and Yu et al proved that there is no dissolution equilibrium in the anodizing process of titanium. 34,[41][42][43] The growth rate of titanium oxide nanotubes reaches 200 nm min À1 , which is much higher than the dissolution rate of titanium oxide in electrolyte (about 1 nm min À1 ). 62 Many references above have negated the FAD dissolution equilibrium, and the three stages of the current-time curve in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Zhang and Yu et al proved that there is no dissolution equilibrium in the anodizing process of titanium. 34,[41][42][43] The growth rate of titanium oxide nanotubes reaches 200 nm min À1 , which is much higher than the dissolution rate of titanium oxide in electrolyte (about 1 nm min À1 ). 62 Many references above have negated the FAD dissolution equilibrium, and the three stages of the current-time curve in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…32,33 Yu et al showed that the growth rate of porous alumina channels was 150 nm min À1 . 20 Even though many facts deny the FAD theory and dissolution equilibrium theory, [32][33][34][35][36][37][38][39][40][41][42][43] many researchers still ambiguously explain various experimental phenomena by applying the FAD and dissolution equilibrium theories. [44][45][46][47] The second model is an oxygen bubble model based on the viscous ow model [48][49][50] and the electronic current theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23] Zhou et al reported that the growth rate of nanotubes in electrolytes with 2 wt% H 2 O was signicantly faster than that in electrolytes with 10 wt% H 2 O. 24 Zhang et al suggested that the growth rate of nanotubes had nothing to do with the concentration of NH 4 F. 25 In addition to studying the effects of water and uoride ions, researchers have also explored many other factors that inuence the growth of anodic TiO 2 nanotubes, such as voltage and temperature. [26][27][28] Mohan et al reported that higher temperature caused a rise in the dissolution rate of oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers also demonstrated that the dissolution of titanium oxide by fluoride ion is also weak. [22][23][24][25] Why is the formation mechanism of porous anodic oxides still controversial up to now? We believe that the main reason is that the relationship between the above field-assisted dissolution reactions and anodizing current has not been clearly understood.…”
Section: Introductionmentioning
confidence: 99%